Managerial Ability and Future Banking Performance: The Role of Book-Tax Differences as Moderator - Eva Herianti; Arna Suryani; Amor Marundha (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to examine and analyze the effect of managerial ability on future banking performance moderated by book-tax differences.Design/Methodology/Approach: The research samples were banks listed on the Indonesia Stock Exchange from 2014 to 2018. A purposive sampling technique was conducted to collect 108 samples of future banking performance (t+1) and 81 samples of future banking performance (t+2). The data were then analyzed using eviews version 10 with the ordinary least square.Research findings: The results showed that managerial ability positively and significantly affected future banking performance (t+1 and t+2), while book-tax differences could reduce the effect of managerial ability on future banking performance (t+1 and t+2).Theoretical contribution/Originality: This study has provided implications to the literature that managers use their abilities to achieve sustainable competitive advantage through efficient and effective use of resources. Managers need an understanding of the relationship between resources, their abilities, competitive advantages, and future earnings achievement.Practitioner/Policy implication: Since managerial ability can increase future banking performance, this study’s results may affect how companies produce managerial ability through efficient use of inputs to produce optimal output that is useful for long-term banking performance.Research limitation/Implication: The conclusion is drawn based on various proxies to measure the managerial ability, book-tax differences, and future banking performance. Further research can develop the managerial ability proxies besides those proposed by Garcia-meca Garcia-Sanchez (2018).